Antibiotic resistance profile of bacteria isolated from raw milk samples of cattle and buffaloes - Tanzin, Tahlina; Nazir, K. H. M. Nazmul Hussain; Zahan, Mst. Nusrat; Parvej, Md. Shafiullah; Zesmin, Khalada; Rahman, Md. Tanvir (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: The objective of this study was to isolate and identify Staphylococcus aureus and Escherichia coli from raw milk samples of cattle and buffalo, and to evaluate the antibiotic sensitivity pattern. Materials and methods: A total of 34 milk samples were collected twice from 17 different healthy cattle (n=14) and buffaloes (n=3) at one-month interval, and analyzed in laboratory by staining, cultural and biochemical characteristics followed by polymerase chain reaction targeting nuc gene of S. aureus and 16 S rRNA of E. coli. Antibiotic sensitivity pattern of the isolated bacteria was assessed using the disc diffusion method. Results: Confirmation of the isolates as S. aureus and E. coli were carried out by PCR using nuc gene, 16S rRNA gene specific primers specific for S. aureus and E. coli respectively. A total of 12 samples (35.29%; 11 from cattle, 1 from buffalo) were found to be positive for S. aureus; 5 and 7 during first and second month, respectively. The E. coli were found in three samples (2 from cattle, 1 from buffaloe); one in first month and two in the second month. The antibiotic sensitivity test using 4 commonly used antibiotics indicated that the most of the isolates were resistant to Gatifloxacin and one isolate showed intermediate resistance to Ofloxacin while sensitive to Ciprofloxacin and Levofloxacin. Conclusion: Two different species of bacteria i.e., S. aureus and E. coli are contaminating with milk samples. The pathogenic bacteria can be controlled effectively by using Ciprofloxacin and Levofloxacin in the case of mastitis in cattle and buffaloes in Bangladesh. http://dx.doi.org/10.5455/javar.2016.c133